The Impact of Process Innovation on Prices: Evidence from Automated Fuel Retailing in The Netherlands - Adriaan R. Soetevent; Tadas Bruzikas (Tinbergen Institute, 2017)
In the last decade, many European countries have seen a sharp increase in the number of automated fueling stations. We study the effect of this process innovation on prices at stations that are automated and their competitors using a difference-in-differences matching strategy. Our estimates show that prices at automated stations drop by 1.0 to 2.1% immediately after conversion and stabilize at this lower level. We find no indication of competitive spillover effects to neighboring sites at the conventional significance levels. Other than previous studies, our estimates do not reveal a difference in impact between early and later adopters of automation.
Keywords: C22; D4; L13; L81; 330; technology adoption; retail gasoline; pricing; competition